ANALISA PENGARUH RETAIL SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION DI TRANSMART CARREFOUR RUNGKUT SURABAYA - Oscar Adam Juanda (Jurnal Strategi Pemasaran, 2019)
This study was conducted to determine the effect of Retail Service Quality on Customer Satisfaction at Transmart Carrefour Rungkut Surabaya.This study is causally using a quantitative approach. The collection of data in a structured way and using statistical methods as the analysis of data. The method used is a survey method that opens a structured questionnaire. This research was conducted by distributing questionnaires to 125 respondents who knew and had visited Transmart Carrefour Rungkut Surabaya . The research method used is a method of quantitative analysis and Simple Linear Regression Analysis using SPSS aplication.